STREAM-AP: um processo para sistematizar a escolha de padrões arquiteturais baseado em requisitos não-funcionais - Silva, Fabio Alexandre Gonçalves (2013)
The importance of non-functional requirements for computer systems is increasing. Satisfying these requirements requires special attention to the software architecture, since an unsuitable architecture introduces greater complexity in addition to the intrinsic complexity of the system. Some studies have shown that, despite requirements engineering and software architecture activities act on different aspects of development, they must be performed iteratively and intertwined to produce satisfactory software systems. The STREAM process presents a systematic approach to reduce the gap between requirements and architecture development, emphasizing the functional requirements, but using the non-functional requirements in an ad hoc way. However, non-functional requirements typically influence the system as a whole. Thus, the STREAM uses Architectural Patterns to refine the software architecture. These patterns are chosen by using non-functional requirements in an ad hoc way. This master thesis presents a process to improve STREAM in making the choice of architectural patterns systematic by using non-functional requirements, in order to guide the refinement of a software architecture